Potential of Bibliographic Tools for Developing Organizational Taxonomies - Chaudhry, Abdus Satta; Wang, Zhonghong; Khoo, Christopher S.G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2014)
Bibliographic tools were used to build an organizational taxonomy in the information studies domain. A classification scheme, three thesauri of indexing terms, and two do-main taxonomies were used to collect categories related to the Information Studies Taxonomy. Classification schemes and thesauri were found helpful in creating the structure and identifying ... Des outils bibliographiques ont été utilisés pour construire une taxinomie organisationnelle dans le domaine des sciences de l’information. Un système de classification, trois thésaurus de termes d’indexation et deux taxinomies du domaine ont été utilisés pour définir les catégories liées à la taxinomie des sciences de l’information. Les systèmes de classification et les thésaurus ont été jugés utiles pour la création de la structure et la définition…